A novel near-infrared and naked-eye fluorescence probe with a large stokes shift for specific detection of cysteine and its application in living cells. Issue 23 (4th June 2020) - Ge, Chunpo; Shen, Fengge; Yin, Yanyan; Zhou, Pingxin; Lu, Chengbiao
Graphical abstract: Highlights: We developed a near-infrared fluorescence probe, TMN-NH2 -Cys. The probe exhibited a large stokes shift. The selective detection of Cys was confirmed by a visible colour change. The probe exhibited a low cytotoxicity. It could be applied to the imaging of endogenous Cys with fluorescence enhancement. Abstract: Cysteine (Cys) is a sulfur-containing nutritional amino acid that plays an important role in the physiological function of living systems. We developed a near-infrared fluorescence probe, TMN-NH2 -Cys . Upon the treatment with Cys, TMN-NH2 -Cys exhibited a large Stokes shift (180 nm) and a visible colour change. TMN-NH2 -Cys can selective detect Cys over homocysteine and glutathione. The probe was synthesised by a simple and high yielding three-step reaction. In addition, the probe exhibited a low cytotoxicity, and could be applied to the imaging of endogenous Cys with fluorescence enhancement.